La influencia de las noticias falsas en la red social Twitter durante las elecciones de la segunda vuelta presencial en Ecuador - Herrera Espinoza, Yomaira Denise (2023)
The general objective of this investigative work Determine the influence of the social network Twitter within the electoral process in Ecuador. For this reason, the topic addressed was developed in a qualitative study, which allowed us to investigate, analyze, collect and verify data through interviews with politicians, which allowed us to have a point of view about fake news. In turn, articles were investigated to determine the legal bases of the topic addressed. The problem details that the information used in social networks lacks reliable sources and credibility, which is complicated by manipulation, given that the number of users who follow the page or social network disseminates that content.